Contrasting Effects of Fasting on Liver-Adipose Axis in Alcohol-Associated and Non-alcoholic Fatty Liver - Rasineni, Karuna; Jordan, Clayton W.; Thomes, Paul G.; Kubik, Jacy L.; Staab, Elizabeth M.; Sweeney, Sarah A.; Talmon, Geoffrey A.; Donohue, Terrence M.; McNiven, Mark A.; Kharbanda, Kusum K.; Casey, Carol A. (Frontiers in Physiology, 2021)
Background: Fatty liver, a major health problem worldwide, is the earliest pathological change in the progression of alcohol-associated (AFL) and non-alcoholic fatty liver diseases (NAFL). Though the cause of AFL and NAFL differ, both share similar histological and some common pathophysiological characteristics. In this study, we sought to examine mechanisms responsible for lipid dynamics in liver and adipose tissue in the setting of AFL and NAFL in response to 48h fasting. Methods: Male rats were fed Lieber-DeCarli liquid control or alcohol-containing diet (AFL model) or chow or high-fat pellet diet (NAFL model). After 6-8 weeks of feeding, half of the rats from each group were fasted for 48h while the other half remained on their respective diets. After sacrifice, blood, adipose and liver were collected for analysis. Results: Even though rats fed both AFL and NAFL diets showed fatty liver, the physiological mechanisms in the development in each was different. Here, we show that increased hepatic de novo fatty acid synthesis, increased uptake of adipose-derived free fatty acids and impaired triglyceride breakdown contribute to the development of AFL. In the development of NAFL, however, increased dietary fatty acid uptake plays a major role. Likewise, the response to starvation in the two fatty liver disease models also varied. While there was a decrease in hepatic steatosis after fasting in ethanol-fed rats, the rats fed the control diet, chow or high-fat diet showed higher levels of hepatic steatosis than their pair-fed counterparts. This diverse response depended on higher adipose lipolysis in all experimental groups except fasted ethanol-fed rats. Conclusions: Even though both AFL and NAFL are histologically indistinguishable, the physiological mechanisms that cause hepatic fat accumulation are different and so are their responses to starvation.